Social Comparison Behaviour on Social Network Sites: The Comparison Between Twitter and Instagram - Mahire Armağan Dündar; Fırat Tufan (Yeni Medya)
The purpose of this study is to examine social comparison behavior on social networking sites (SNS). Quantitative research method based on the closed-ended questionnaire technique was used in the study in which social comparison behavior was examined on image-based SNS, Instagram and text-based SNS, Twitter. Findings show that; individuals make social comparisons more in physical environments than on SNS. The level of social comparison is higher on Instagram compared to Twitter. Individuals are more frequently engaged in upward comparisons than downward comparisons on both Instagram and Twitter. Wealth is the domain in which individuals make comparisons the most on Instagram while the prominent comparison domain on Twitter is success. Inspiration is an emotion experienced most by individuals towards upward comparisons, whereas sympathy is the most experienced emotion by individuals towards downward comparisons on both Instagram and Twitter. There is no relation between social comparison level and frequency of SNS use.